Vision complaints are the impact of using laptops during online learning - Muhammad Iqbal Ilyasa; Sri Wahyu Basuki (Universitas 'Aisyiyah Yogyakarta, 2023)
The high use of laptops and computers that support online learning activities during the Covid-19 pandemic requires students to take part in online learning so that they become dependent on using laptops. Long-duration of laptop use and bad habits are associated with visual impairment. This study aims to understand the relationship between duration and position when using a laptop in online learning with vision complaints in students of the Faculty of Medicine, University of Muhammadiyah Surakarta, class of 2018. This research method uses Analytical Observational with Cross Sectional approach. The number of samples in this study was 117 students. This study identified the relationship between the duration and position of laptop use during online learning on vision complaints using Google Forms with questions that addressed variables that could affect the study with univariate and multivariate analysis. Results: Multivariate analysis of dominant laptop use affected vision complaints (p = 0.05). Duration of laptop uses p=0.050, the position of laptop use p=0.271. Conclusion: Duration influences vision complaints, while position does not influence vision complaints due to laptop use during online learning.